Performance prediction for solar air heater having rectangular sectioned tapered rib roughness using CFD. (December 2017) - Gupta, A.D.; Varshney, L.
Highlights: 3D CFD simulation is performed on a solar air heater for heat transfer and pressure drop. Impact of flow and configuration parameters on the performance index is investigated. The maximum enhancement ratio in Nu is 2.56 for Re 12, 000 in the present work. Performance index is found to vary from 1.31 to 1.91 in the range of parameters investigated. Abstract: In the present work CFD analysis of a solar air heater (SAH) duct provided with artificial roughness in the form of rectangular sectioned tapered rib has been performed using Ansys FLUENT. Twelve different configurations of tapered rib with taper angle, αt of 1.6°, 2.3° and 3.2° for pitch of 10, 15, 20 and 25 mm and constant rib width, wr  = 0.7 mm have been considered as roughness element. A three-dimensional non-uniform hybrid grid is generated according to the configuration using cutcell method. The differential equations involved in the model are solved with a finite-volume-based numerical method. The RNG k–ε turbulence model with enhanced wall function is used to solve the transport equations for turbulent flow and energy dissipation rate. Effect of roughness parameters namely tapered angle and relative roughness pitch on Nusselt number and friction factor for a constant value of heat flux (1000 W/m 2 ) is discussed. The optimal values of geometrical parameters are obtained on the basis of the performance index in the range of Reynolds number 3800–18, 000. Optimum performance index is found to be 1.91 corresponding to the αt of 1.6° and relative roughness pitch, P/e of 10.7 at Reynolds number, Re of 12, 000.